Static and dynamic 68Ga-FAPI PET/CT for the detection of malignant transformation of intraductal papillary mucinous neoplasia of the pancreas - Lang, Matthias; Spektor, Anna-Maria; Hielscher, Thomas; Hoppner, Jorge; Glatting, Frederik M.; Bicu, Felix; Hackert, Thilo; Heger, Ulrike; Pausch, Thomas; Gutjahr, Ewgenija; Rathke, Hendrik; Giesel, Frederik L.; et al. (Journal of nuclear medicine, 2023)
Pancreatic ductal adenocarcinoma (PDAC) may arise from intraductal papillary mucinous neoplasms (IPMN) with malignant transformation, but a significant portion of IPMN remains to show benign behavior. Therefore, it is important to differentiate between benign IPMN and IPMN lesions undergoing malignant transformation. However, nonoperative differentiation by ultrasound, CT, MRI, and carbohydrate antigen 19-9 (CA19-9) is still unsatisfactory. Here, we assessed the clinical feasibility of additional assessment of malignancy by PET using 68Ga-labeled fibroblast activation protein inhibitors (68Ga-FAPI PET) in 25 patients with MRI- or CT-proven cystic pancreatic lesions. Methods: Twenty-five patients with cystic pancreatic lesions who were followed up in the European Pancreas Center of Heidelberg University hospital and who were led to surgical resection or fine-needle aspiration due to suspicious clinical, laboratory chemistry, or radiologic findings were examined by static (all patients) and dynamic (20 patients) 68Ga-FAPI PET. Cystic pancreatic lesions were delineated and SUVmax and SUVmean were determined. Time–activity curves and dynamic parameters (time to peak, K1, k2, K3, k4) were extracted from dynamic PET data. Receiver-operating curves of static and dynamic PET parameters were calculated. Results: Eleven of the patients had menacing IPMN (high-grade IPMN with [6 cases] or without [5 cases] progression into PDAC) and 11 low-grade IPMN; 3 patients had other benign entities. Menacing IMPN showed significantly elevated 68Ga-FAPI uptake compared with low-grade IPMN and other benign cystic lesions. In dynamic imaging, menacing IPMN showed increasing time–activity curves followed by slow decrease afterward; time–activity curves of low-grade IPMN showed an immediate peak followed by rapid decrease for about 10 min and slower decrease for the rest of the time. Receiver-operating curves showed high sensitivity and specificity (area under the curve greater than 80%) of static and dynamic PET parameters for the differentiation of IPMN subtypes. Conclusion: 68Ga-FAPI PET is a helpful new tool for the differentiation of menacing and low-grade IPMN and shows the potential to avoid unnecessary surgery for nonmalignant pancreatic IPMN.